2018
DOI: 10.1155/2018/6260724
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Aged and Seriously Damaged RC Beams Strengthened Using CFRP Composites

Abstract: This paper presents results from experiments on aged and seriously damaged reinforced concrete (RC) beams strengthened with different arrangements of external carbon fiber-reinforced polymer (CFRP) laminates and end anchorages. Seven RC beams from an old bridge, measuring 250 × 200 × 2300 mm, were tested. All specimens were loaded to yield load to evaluate initial mechanical properties. Then, these seriously damaged specimens were repaired using different CFRP-reinforcing schemes and reloaded to failure. The y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…But, it does not take into account the variation in confinement effect due to changes in chamfer radius of section corners (i.e., the impact of effective confinement area A e ) in rectangular sections. Moreover, it does First, authors set the cross-sectional shape factors C in equations (2), (4), (5), (7), (8), and (9) as functions of the effective confinement area ratio α e instead of fixed values. e previous Nakatsuka's work [13] used ϕ150 × 300 mm round specimens and 150 × 150 × 300 mm square specimens (with chamfer radius R equal to 30 mm for all).…”
Section: Expansion Of Evaluation Formulas For the Constitutivementioning
confidence: 99%
See 3 more Smart Citations
“…But, it does not take into account the variation in confinement effect due to changes in chamfer radius of section corners (i.e., the impact of effective confinement area A e ) in rectangular sections. Moreover, it does First, authors set the cross-sectional shape factors C in equations (2), (4), (5), (7), (8), and (9) as functions of the effective confinement area ratio α e instead of fixed values. e previous Nakatsuka's work [13] used ϕ150 × 300 mm round specimens and 150 × 150 × 300 mm square specimens (with chamfer radius R equal to 30 mm for all).…”
Section: Expansion Of Evaluation Formulas For the Constitutivementioning
confidence: 99%
“…Conversely, the ratio C exp /C est also becomes large as the longitudinal ratio d/b increases for ε T in Figure 10(b) and ε R in Figure 10(d). In this paper, authors modified the evaluation formulas for four components: E BT , ε T , E TR , and ε R from equations (5), (7), (8), and (9) to the following in order to take the longitudinal ratio d/b into account:…”
Section: Constitutive Law For Rectangularmentioning
confidence: 99%
See 2 more Smart Citations
“…As an effective alternative to traditional materials for strengthening and repairing damaged structures, CFRP-reinforced bridge structure has been extensively investigated (Lu et al, 2018;Peng et al, 2014;Hosseini et al, 2019;Shukri et al, 2018;Mashrei et al, 2019). Zhuang et al (2018) conducted an experimental study on the CFRP reinforced seriously damaged concrete beam. Different parameters were investigated and it demonstrated that CFRP plate can have good contributions to the performance of the damaged concrete beams.…”
Section: Introductionmentioning
confidence: 99%